2019
DOI: 10.1108/arj-02-2018-0035
|View full text |Cite
|
Sign up to set email alerts
|

Board gender composition, dividend policy and COD: the implications of CEO duality

Abstract: Purpose This study aims to examine whether CEO duality affects the association between board gender composition, dividend policy and cost of debt (COD). Design/methodology/approach The S&P 1500 firms’ data for this study were collected from the Bloomberg professional service terminal for the period 2010-2015. Findings The results show that board gender composition positively impacts both a firm’s propensity to pay dividends and the level of payouts. However, this positive association is only present in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
25
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 63 publications
9
25
2
3
Order By: Relevance
“…The findings of this study are consistent with a study by McGuinness et al (2015) that no significant relationship exists between female directors and dividend payout rates in China. However, the results of this study do not support a study by Benjamin & Biswas (2019) who analyzed the Bloomberg Firms S&P 1500. They indicated that gender composition had a favorable influence on the dividend payout rate.…”
Section: Female Board Of Director and Dividends Policycontrasting
confidence: 99%
“…The findings of this study are consistent with a study by McGuinness et al (2015) that no significant relationship exists between female directors and dividend payout rates in China. However, the results of this study do not support a study by Benjamin & Biswas (2019) who analyzed the Bloomberg Firms S&P 1500. They indicated that gender composition had a favorable influence on the dividend payout rate.…”
Section: Female Board Of Director and Dividends Policycontrasting
confidence: 99%
“…Menurut (Benjamin & Biswas, 2019) menyatakan bahwa sebutan gembala dapat disamakan dengan kepemimpinan yang eksemplaris atau kepemimpinan yang memberi contoh. Jika gembala yang seharusnya menjadi berkat bagi jemaatnya dengan memimpin mereka kepada rumput yang hijau dan air yang tenang melalui keteladannya agar pertumbuhan mereka terjadi, dan dengan demikian pertumbuhan gereja juga semakin nyata justru merugikan dan mengecewakan mereka, apa yang dapat diharapkan dari gereja?…”
Section: Pendahuluanunclassified
“…Firman Tuhan dengan jelas memerintahkan seorang hamba Tuhan untuk menggembalakan domba-domba Allah yang dipercayakan padanya dengan cara menjadi teladan bagi mereka (1 Petrus 5:1-3). (Benjamin & Biswas, 2019) menggambarkan gembala selaku hamba Tuhan sebagai pemimpin yang eksemplaris atau dengan kata lain pemimpin yang memberi contoh.…”
Section: Pendahuluanunclassified